2018
DOI: 10.1126/scisignal.aat2214
|View full text |Cite
|
Sign up to set email alerts
|

Biased antagonism of CXCR4 avoids antagonist tolerance

Abstract: Repeated dosing of drugs targeting G protein–coupled receptors can stimulate antagonist tolerance, which reduces their efficacy; thus, strategies to avoid tolerance are needed. The efficacy of AMD3100, a competitive antagonist of the chemokine receptor CXCR4 that mobilizes leukemic blasts from the bone marrow into the blood to sensitize them to chemotherapy, is reduced after prolonged treatment. Tolerance to AMD3100 increases the abundance of CXCR4 on the surface of leukemic blasts, which promotes their rehomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…Unexpectedly, the effect of Gal‐3 CRD was not accompanied by reduced internalization of CXCR4 (Fig D), which is mediated by β‐arrestin recruitment . However, it has been reported that chemokine receptors may signal in a biased fashion, with β‐arrestin recruitment and internalization being uncoupled .…”
Section: Resultsmentioning
confidence: 75%
“…Unexpectedly, the effect of Gal‐3 CRD was not accompanied by reduced internalization of CXCR4 (Fig D), which is mediated by β‐arrestin recruitment . However, it has been reported that chemokine receptors may signal in a biased fashion, with β‐arrestin recruitment and internalization being uncoupled .…”
Section: Resultsmentioning
confidence: 75%
“…So far, AMD3100 is the only CXCR4 unbiased antagonist approved for the use in the clinic, which blocks the activity of both G proteins and β-arrestins, and is also able to inhibit the function of the CXCL12/HMGB1 heterocomplex ( 6 ). To avoid development of tolerance induced by the use of AMD3100, other approaches to block the activity of CXCR4 have been exploited including the use of peptides with biased activity ( 17 ). In addition, the emerging concept that β-arrestins can support both G-protein-dependent and -independent signaling pathways ( 18 ) has fostered our research for a better understanding of the role of β-arrestins in promoting the activity of the CXCL12/HMGB1 heterocomplex.…”
Section: Introductionmentioning
confidence: 99%
“…Most strategies directly antagonize the GPCR (for excellent review, see Reference [108]). Although very successful in some cases, attested by the example of plerixafor [143] and maraviroc [144], the respective antagonists of CXCR4 and CCR5, most of the pharmacological agents that target chemokine receptors inhibit both G protein signaling and β-arrestins-mediated endocytosis, promoting receptor accumulation at cell surface, a process called “antagonist tolerance” [145]. As a result, the efficacy of this type of antagonist is reduced after a long time of treatment.…”
Section: Chemokines In Copd: Therapeutic Implicationsmentioning
confidence: 99%